2014
DOI: 10.1517/17425255.2015.992414
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen genetic risk factors of drug-induced liver toxicology

Abstract: Increasing evidence points to a crucial role for the adaptive immune system in the pathogenesis of DILI. Identification of specific HLA alleles as risk factors through large genome-wide association studies has been instrumental in this and in vitro analyses have facilitated improved understanding of the molecular mechanisms. This provides the basis for developing clinical pharmacogenomic applications. Already, genotyping for hypersensitivity HLA risk alleles has been implemented and opportunities for pre-presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 94 publications
1
26
0
1
Order By: Relevance
“…Our study provides strong evidence that prospective HLA‐B*35:01 screening may identify patients with the greatest risk of PM‐DILI, such as HLA‐A*31:01 testing for carbamazepine‐induced hypersensitivity and HLA‐B*57:01 screening for hypersensitivity to abacavir . Despite the small sample sizes of subjects included in this work, our data were significant and in line with other GWAS demonstrating an association of HLA genotype and DILI susceptibility . Based on the assumption that the approximate prevalence of PM‐DILI is 8.3% (6/72) in Han Chinese, the HLA‐B*35:01 allele increases the risk of DILI to 37% (3/8), whereas the risk of DILI in noncarriers is 4.7% (3/64).…”
Section: Discussionsupporting
confidence: 78%
“…Our study provides strong evidence that prospective HLA‐B*35:01 screening may identify patients with the greatest risk of PM‐DILI, such as HLA‐A*31:01 testing for carbamazepine‐induced hypersensitivity and HLA‐B*57:01 screening for hypersensitivity to abacavir . Despite the small sample sizes of subjects included in this work, our data were significant and in line with other GWAS demonstrating an association of HLA genotype and DILI susceptibility . Based on the assumption that the approximate prevalence of PM‐DILI is 8.3% (6/72) in Han Chinese, the HLA‐B*35:01 allele increases the risk of DILI to 37% (3/8), whereas the risk of DILI in noncarriers is 4.7% (3/64).…”
Section: Discussionsupporting
confidence: 78%
“…An example of the possible clinical relevance of the pi hypothesis has been proposed for the hepatotoxic drug ximelegatran since the drug does not covalently bind proteins to form neoantigens. However, in vitro studies have shown a direct inhibition by ximelegatran of peptide binding to HLA DRB1*0701, supporting direct interaction of the drug with this HLA binding site [112]. …”
Section: Pathogenesis Of Idiosycratic Drug-induced Liver Injury (Imentioning
confidence: 99%
“…Blood pyrrole–protein adducts have been proposed for pyrrolizidine‐DILI 16. Also, genome‐wide association studies have linked certain human leukocyte antigen (HLA) alleles with DILI; examples include HLADRB1*1501 in amoxicillin–clavulanate17 and HLA‐A*33:01 for a cholestatic or mixed pattern of DILI 18. The index case was diagnosed as DILI‐ALF based on history, exclusion of other etiologies as per American College of Gastroenterology guidelines, temporal correlation, postmortem liver biopsy findings, and RUCAM score 8…”
Section: Discussionmentioning
confidence: 99%